Toward sustainable management: Southern Africa's Afromontane, and Western Australia's jarrah forests - Wardell-Johnson, Grant; Calver, M. (Millpress, 2005)
We review the history of forest management in two southern hemisphere forest types: Western Australia's jarrah Eucalyptus marginata forests and the Afromontane forests of southern Africa to determine approaches for achieving sustainable forest management. We argue that despite major differences in the ecology and bio geography of these two forest types, a shared pattern in the history of exploitation may provide lessons for achieving sustainable management across forest types. While advanced silvicultural understanding has long been achieved in both forest types, this in itself has not led to either sustainable management or to public acceptance of forest management regimes. In both areas an early, rapid expansion of uncontrolled timber removal and in the number of operating timber mills was followed by controlled exploitation, a rapid decline in the numbers of mills and, more recently, a general decline in yield. In neither case was increased concern about conservation responsible for the reduction in either yield or in employment in the industry. Rather, in WA jarrah forests, amendments in purpose and tenure were subsequent to the loss of most mills and towns, while in southern Africa's Afromontane forests, timber workers were pensioned by 1939 because of scanty remaining merchantable timber. In the jarrah forests, we believe that the conflict generated by conservation concerns, reduced timber industry employment, and reduced benefits flowing to the communities adjacent to the logged forests, has fueled dissatisfaction with forest management outcomes.This has led to a new process in the preparation of forest management plans. Increased accountability and more realistic expectations of timber yield following productivity declines may mean the current plan for the forests of Western Australia can be used as an example to achieve sustainability in Mediterranean forest ecosystems. However, general acceptance of management regimes may not be achieved until the scale of logging operations is matched with local sustainability criteria. Increasing the area of reserves will not accelerate this process, but rather may impede it. Setting conservative overall yield estimates, and achieving local sustainability seem both to be necessary to achieve general acceptance of management regimes. A sustainable management system appears to have been achieved in the Afromontane forests and has led to the development and maintenance of support for small-scale operations to supply local timber needs from State managed forests. In both environments such a process is achievable because of the high value and specialized nature of the native forest timber resource, and because of the increasing availability of general purpose timber from plantations.